THE ROLE AND SIGNIFICANCE OF IDIOMS IN ENGLISH AND UZBEK LINGUISTICS - Mirzatolipova Gulzira , (TADQIQOTLAR.UZ, 2024)
Abstract: This article highlightes the importance and usage of phraseological units in two languages. At the same time, the interdependence and difference of Uzbek and English phraseological units, their translation forms are studied comparatively.